HOMO SOLITARIUS IN SHORT STORIES BY VASYL STEFANYK - Derkachova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article highlights the problem of a lonely man in Vasyl Stefanyk’s short stories. It is noticed that the writer mentions fear and loneliness not only in short stories but also in his letters, and defines their nature: fear of unsettled life, hunger, cold, fear of losing loved ones, fear of loneliness, nightmares, the tragedy of ordinary person. It is determined that often Stefanyk’s characters become lonely, forced, under the pressure of external circumstances. Old age and illness are the main causes of loneliness. Such heroes often find themselves a few steps away from the terrible phantasmagoric death and meet it in their home, where they no longer feel themselves protected. The native house becomes a place of danger, threat, anxiety, acting as a place of horror. There, the heroes have terrible pre-death visions, some try to get out of this locus, but are defeated. Someone succeeds, and he hopes for the best. It is concluded that homo solitarius in Vasyl Stefanyk’s short stories are mostly old people who perceive loneliness as one of the inevitable stages of their lives. It is often inseparable from death. Homo solitarius are mostly silent or talk to animals, themselves, objects in the house, immersed in the past. Loneliness-death is inevitable and inevitable for them. They don’t protest, do not resist, understanding the futility of resistance and the depth of fate. The following short stories were mentioned: «Novyna», «Sama-Samiska», «Maister», «Leseva familiia», «Osin», «Pokhoron», «Skin», «Shkoda», «Anhel», «Dity», «Sviatyi vechir», «Palii», «Vona – zemlia», «Mariia»The main emphasis is on the works of the first period of Vasyl Stefanyk (1897 – 1901).